An Evaluation of Waste Implementation of Poly Clinic's Outstanding Services with Blueprint Service to Reduce Waiting Time on Kisaran Asahan District - Dwi Astuti Manullang; Chrismis Novalinda Ginting; Sri Wahyuni Nasution; Gusbakti Rusip; Mangatas Silaen (Budapest International Research and Critics University, 2022)
The quality of health services provided to patients should be observed and addressed as well as possible so that patients as hospital customers can be loyal/loyal to the hospital. In this study, one aspect that needs to be improved is the outpatient service aspect. The outpatient unit is the patient's entry gate to the hospital in addition to the emergency unit. Outpatient visits exceed emergency department visits. The tendency of the community towards polyclinic services is increasing to get practical treatment services that come once and on that day also get complete services (one daycare) (Dewi et al., 2020) Installation of care in the hospital consists of installations inpatient, and outpatient. Outpatient installation is a service used by doctors as a place for consultation, examination, and treatment of patients who require a short time (Ministry of Health, 2012).